Electronic Government Development Strategies Using Frameworks COBIT 5 - Novianto, Fanny (Proceeding International Conference on Science and Engineering, 2020)
At this time, Information technology in the government or called by electronic government (e-government) is an absolute necessity and must be continuously developed as an acceleration tool in strategic policy and decision making. Utilization of e-government aims to improve performance and productivity, improve budget efficiency, transparency and accountability in the delivery of service activities to the communities. The incessant use of e-government in the government both central and regional, of course, not only produces benefit or value to the organization, but also gives a variety of problems and obstacles. To guarantee the benefit and value by using e-government and minimize various problems and obstacles, it is necessary to build information technology governance in the e-government development. In the information technology governance, an organization does not only build information technology facilities and infrastructure, but how information technology is used be able to achieve organizational goals, is able to play a role in the organization's strategic decision making processes and policies and remains in harmony with the architecture framework of information technology development that is has been established. To achieve information technology good governance, strategies are needed in developing existing e-government. The first step is to evaluate the implementation of e-government. Evaluation is done by measuring the level of maturity of e-government that has been applied. This measurement includes a strategic plan for information technology management, maintenance of information technology facilities and infrastructure, management of information technology services that are sustainable and the last is oversight of information technology governance. The scope of this research is e-government which has been implemented in the Ministry of Law and Human Rights in the Special Region of Yogyakarta. The research method used is a quantitative method using a questionnaire instrument and using the 5th edition of the Control Objective for Information and Related Technology (COBIT) framework model to determine the level of maturity in the information technology governance process. This study will provide an overview of information technology governance has been implemented and produce recommendations that is needed to improve and develop a comprehensive information technology governance.